Threshold regression with endogeneity for short panels - Tue Gørgens; Allan H. Würtz (Econometrics, 2019)
This paper considers the estimation of dynamic threshold regression models with fixed effects using short panel data. We examine a two-step method, where the threshold parameter is estimated nonparametrically at the N-rate and the remaining parameters are estimated by GMM at the ÍN-rate. We provide simulation results that illustrate advantages of the new method in comparison with pure GMM estimation. The simulations also highlight the importance of the choice of instruments in GMM estimation.
Keywords: C23; C24; C26; 330; threshold regression; dynamic models; endogeneity; panel data; GMM estimation; integrated difference kernel IDK estimator; superconsistency